Sikap Diskriminatif Donald Trump terhadap Isu Rasial dan Etnis Menjelang Pemilihan Presiden Amerika Serikat 2020 - Pawestri, Giovanna Pramudita; Erawan, I Ketut Putra; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2023)
The issue of discrimination is still relevant in various parts of the world in this contemporary era. It is undeniable that history plays an important role in how the construction of discrimination can stand firm to this day. One World War II actor, Adolf Hitler, in his various speeches and writings, spread his belief in the purity and superiority of the German race which was believed to be the ruling race / Arya (master race). Meanwhile, in this contemporary era, the 45th president of the United States of America Donald Trump also discriminates against minority identity groups in the United States. This is supported by Donald Trump's policies and several statements containing discriminatory elements during his term as president of the United States of America. The construction of domination of an identity group like what Trump is trying to do is based on political interests. Through power over access, the economy, and social structure will be formed as this also creates gaps against minority identity groups. Keywords: Discrimination, Donald Trump, Identity.